English Meeting: Enhancing English Public Speaking Skills Through The T.A.I.L.–S.T.A.R.T.–C.L.O.S.E. Framework And Body Language Training For English Education Students At Universitas Islam Makassar - Muthmainnah Mursidin; Sitti Nurjannah; Ida Ilmiah Mursidin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This community service program was designed to strengthen the English public speaking competence of students in the English Education Study Program at Universitas Islam Makassar. The activity addressed recurring difficulties in organizing self-introductions, opening and closing presentations, and maintaining effective non-verbal delivery. A practice-based workshop was developed around three mnemonic frameworks: T.A.I.L. for self-introduction, S.T.A.R.T. for presentation openings, and C.L.O.S.E. for presentation closings, supported by training in seven elements of body language. The program used guided modelling, individual writing, paired rehearsal, short presentation challenges, peer feedback, self-reflection, and facilitator observation. Evaluation focused on the structure of participants’ speaking scripts, clarity of delivery, use of transitions, audience engagement, and awareness of eye contact, posture, gesture, facial expression, voice, strategic pauses, and movement. The implementation indicated that the mnemonic frameworks helped participants organize ideas more quickly and reduced their dependence on improvised or repetitive expressions. Participants also demonstrated more purposeful openings and closings and greater attention to non-verbal delivery. Pronunciation consistency, spontaneous responses, and sustained fluency remained areas requiring continued practice. The program shows that a compact, scaffolded, and highly participatory English Meeting can serve as a practical model for extracurricular speaking development in higher education.